1988
DOI: 10.1038/icb.1988.48
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic and immunoblot analysis of Cryptosporidium oocysts

Abstract: Summary Cryptosporidium oocysts were recovered by density gradient centrifugation from diarrhoeal faeces of four human patients and one goat kid. Goat-derived oocysts were further treated with excystation medium and the excysted oocyst walls purified by isopycnic ultracentrifugation. Soluble extracts from intact oocysts and the oocyst wall preparation were analysed by SDS-PAGE. Fifty-one polypeptide bands were detected in intact oocyst preparations: 48 were in the range 14 000-200 000 molecular weight (MW), tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 18 publications
2
22
1
Order By: Relevance
“…Proteins present in Cryptosporidium isolates have been characterized previously (28); however, amylopectin granules and residual bodies were not removed from oocyst walls prior to SDS-PAGE analysis. Because the residual bodies have not been fully characterized, SDS-PAGE analysis of excysted oocysts containing residual bodies may produce bands that are not truly associated with the oocyst wall.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins present in Cryptosporidium isolates have been characterized previously (28); however, amylopectin granules and residual bodies were not removed from oocyst walls prior to SDS-PAGE analysis. Because the residual bodies have not been fully characterized, SDS-PAGE analysis of excysted oocysts containing residual bodies may produce bands that are not truly associated with the oocyst wall.…”
Section: Discussionmentioning
confidence: 99%
“…Results of recent studies (314)(315)(316) compared with others (191,192,215,315,334) suggest that at least two C. parvum sporozoite surface proteins are being confused. A 23-kDa molecule is weakly labeled by iodination (315), is highly immunogenic (191,192,215,334), and may have several epitopes that cross-react with some higher-molecular-size species (192,215). An 18-to 20-kDa protein, often referred to as P20, is intensely labeled by iodination (315) and appears to be less immunogenic than P23.…”
Section: Potential Sporozoite and Oocyst Antigensmentioning
confidence: 99%
“…The oocysts were concentrated, purified, solubilized, electrophoresed in a 12% sodium dodecyl sulfate polyacrylamide gel (SDS-PAGE) and then transferred to nitrocellulose filter paper as described previously (2). The strip of filter paper containing the 23 000 MW antigen was excised and then dissolved in a small volume of dimethyl sulfoxide and diluted in an equal volume of pyrogen-free saline.…”
Section: Faeces Containingmentioning
confidence: 99%
“…Because immunocompetent hosts usually recover spontaneously and prove refractive to reinfection, various immunological studies have been performed to identify parasite antigens using immune sera from naturally infected hosts. Immunoblot studies have resulted in the detection of a small molecular weight (MW) antigen (20 000-23 000 MW) in either intact oocyst or sporozoite life cycle stages which is frequently recognized by acute and convalescent sera from humans, goats, cattle and horses (1)(2)(3). However, radiolabelling of intact oocysts with '2^1 failed to locate this antigen on the exterior oocyst wall (2), whereas fluorescent-antibody studies indicated it may be located on the sporozoite and merozoite membranes (3).…”
Section: Introductionmentioning
confidence: 99%